Normative Study against Limitation of Liability Notary Deed in Lieu In Making Based Act No. 2 of 2014 on Notary - Isman Isman; Ahmadi Ahmadi; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to analyze: 1) the role of the Notary Deed in Lieu in manufacturing. 2) Limitation of liability in the manufacture Substitute Notary Deed. 3) Barriers and solutions for Substitute Notary in carrying out its responsibilities in the manufacture of Deeds pursuant to Act No. 2 of 2014 On Notary.This research is normative juridical approach, with specification of descriptive analysis. The collection of primary and secondary data obtained by interview and literature.The research results are: 1) Substitute Notary important role in meeting the needs of the people in deed, Substitute Notary is only temporary, as it replaces the notaries who are on leave, sick or absent or unable to perform its functions properly. So that the public service to create an authentic deed is not disturbed and running as it. 2) Limitation Substitute Notary Responsibility and authority is not affected by age restrictions as well as Notary, despite all the deed made by Notary Substitute, has been assigned or transferred to the depositary Protocol Notary, this means that although already quit or retired as a Notary, the Notary still be responsible for the deed he made. 3) Barriers for Substitute Notary in carrying out its responsibilities in the manufacture of Deed is the lack of experience of the notary, limited capacity and their doubts about the substitute notary office. Solutions that can be done is to provide socialization and guidance of the MPD to the Notary Substitute related to the duties and responsibilities as a Substitute Notary.Keywords: Responsibility Notaries; Notary Substitute Deed.